Dielectric properties and activation energies of Cu: ZnO dispersed nematic mesogen N-(4-methoxybenzylidene)-4-butylaniline liquid crystal. Issue 9 (15th July 2020) - Misra, Abhishek Kumar; Tripathi, Pankaj Kumar; Pandey, Kamal Kumar; Singh, Bhupendra Pratap; Manohar, Rajiv
Abstract: In present work, Cu:ZnO nanoparticles (NPs) used to disperse in pure nematic liquid crystal N-(4-methoxybenzylidene)-4-butylaniline (MBBA). Due to their larger dipole moment of NPs have stronger interactions with the liquid crystal molecules which lead to enhance the ordering of the nematic molecules as demonstrated by the increase in the value of mean dielectric permittivity. The dispersion of Cu:ZnO NPs on the dielectric behavior and activation energies as a function of temperature and frequency has studied for various concentrations of Cu:ZnO NPs. The complex dielectric permittivity and the relaxation frequency are dependent on the concentration of Cu:ZnO NPs. Theoretically obtained activation energy and relaxation times (Slater's perturbation equations) have been found in good agreement with experimental results. An effort has been made to explain these results on the basis of interaction between nematic molecules and NPs. GRAPHICAL ABSTRACT: